DESIGN OF NORMAL CONCRETE AND CONCRETE FIBERS WITH TANAHMERAH SAND AND CRUSHED STONE KUTAI BARAT - JUDIN, NASRA (KURVA S JURNAL MAHASISWA, 2014)
Final Project Faculty of Civil Engineering Department of the University of August 17th 1945 Samarinda.Normal concrete is concrete that has a weight of 2200 - 2500 kg / m3 using natural aggregates were broken or without broken.Fiber-reinforced concrete is a mixture of concrete plus fiber, generally in the form of rods with a size of 5-500 μm with a length of about 25 mm. Fiber material may be asbestos fibers, plastic fibers (polypropylene), or a piece of steel wire. The fibers in concrete prevents cracks that makes concrete more ductile than ordinary concrete. The purpose of this study was to compare the compressive strength value produced normal concrete and fiber-reinforced concrete that uses coarse crushed aggregate of Kampung Keay Kutai Barat and fine aggregate from Tanah Merah North Samarinda.This study uses a mix design method (Indonesian National Standard) SNI 03-2847-2002 conducted in the laboratory using the maximum size of coarse aggregate is 40 mm. The sample used for normal concrete and concrete variation of 0.25% coconut fiber and a variation of 0.5% respectively using 30 samples and the total number of samples is 90 samples.From the test results normal concrete compressive strength at 28 days compressive strength value of the average need (f'cr) is 108.050 and the compressive strength implied (f'c) is 87.987 kg / cm2 of the average compressive strength needs to be targeted ( f'cr) = 250 kg / cm2 and the compressive strength implied (f'c) = 175 kg / cm2. Concrete compressive strength testing of fiber variation of 0.25% at 28 days the value of the average compressive strength of the targeted (f'cr) is104.576 kg / cm2 and the compressive strength implied (f'c) is 82.261 kg / cm2 of compressive strength average need targeted (f'cr) = 250 kg / cm2 and the compressive strength implied (f'c) = 175 kg / cm2. Concrete compressive strength testing of fiber variation of 0.5% at 28 days the compressive strength average (f'cr) is 96.408 kg / cm2 and the compressive strength implied (f'c) is 75.994 kg / cm2 from the mean compressive strength average need targeted (f'cr) = 255 kg / cm2 and the compressive strength implied (f'c) = 175 kg / cm2.